2019
DOI: 10.25259/sni_339_2019
|View full text |Cite
|
Sign up to set email alerts
|

Which factors predict the loss of cervical lordosis following cervical laminoplasty? A review of various indices and their clinical implications

Abstract: Background: Many patients undergoing laminoplasty develop postoperative loss of cervical lordosis or kyphotic alignment of cervical spine despite sufficient preoperative lordosis. This results in poor surgical outcomes. Methods: Here, we reviewed the relationship between multiple radiological parameters of cervical alignment that correlated with postoperative loss of cervical lordosis in patients undergoing laminoplasty. Results: Patient with a high T1 slope (T1S) has more lordotic alignment of the cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this regard, the T1 slope (T1s) has been spotlighted recently [ 31 ]. However, the influx of too many new predictive factors can cause confusion in the analysis of patients’ information [ 61 , 63 ]. In this study, we present an overview of the sagittal alignment parameters that might predict clinical or radiological results through a literature review.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the T1 slope (T1s) has been spotlighted recently [ 31 ]. However, the influx of too many new predictive factors can cause confusion in the analysis of patients’ information [ 61 , 63 ]. In this study, we present an overview of the sagittal alignment parameters that might predict clinical or radiological results through a literature review.…”
Section: Introductionmentioning
confidence: 99%
“…In the present prospective study, both preoperative C2-7 angle and T1S were significantly smaller in the kyphosis group than in the lordosis group, and C1-7 SVA before surgery showed no significant difference between the 2 groups. In contrast to these results, a literature review showed that patients both with preoperative more lordotic cervical spine and high T1S are at increased risk for the loss of cervical lordosis after laminoplasty, 12 and Sakai et al 3 reported that cervical regional sagittal imbalance was a preoperative risk factor for cervical kyphotic deformity after laminoplasty for CSM in patients without preoperative cervical kyphosis. The reason why these results in this study were opposed to those in these previous reports remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…In patients undergoing cervical fusion, Sharma et al found a strong correlation between TS-CL and cSVA. They showed that the mismatch of TS-CL over 20° was associated with cSVA over 4 cm [ 35 ]. However, TS-CL cannot be obtained directly from the standard neutral lateral radiographs.…”
Section: Discussionmentioning
confidence: 99%